2016
DOI: 10.2965/jwet.16-022
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Enterotoxin Gene-positive <i>Clostridium perfringens</i> Spores among Human and Livestock Samples and its Potential as a Human Fecal Source Tracking Indicator

Abstract: In this study, to evaluate whether Clostridium perfringens could be a useful fecal indicator in aquatic environments and could be employed as a potential source-tracking indicator, the distribution of C. perfringens spores and their toxin types in sewage and livestock fecal samples were analyzed. A total of 804 C. perfringens spore isolates (366 from human-related sewage and effluents, 128 from cattle, 129 from pigs, 72 from chicken, and 109 from abattoir wastewaters) were analyzed using multiplex polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
3
12
1
Order By: Relevance
“…Finally, the isolates from humans infected by asari clams may become a pollution source of water environment via sewage influents and effluents when the impact of asari clams on human infection is significant. The isolation rates of type F C. perfringens were 80%, 56%, and 9% from influents, effluents, and asari clams, respectively, which were higher than the previous report of 29% and 32% from influents and effluents, respectively [ 18 ]. The differences in isolation rates may be because of the difference in the amount of samples to be cultured in an enrichment broth and that in the geographical circumstances.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Finally, the isolates from humans infected by asari clams may become a pollution source of water environment via sewage influents and effluents when the impact of asari clams on human infection is significant. The isolation rates of type F C. perfringens were 80%, 56%, and 9% from influents, effluents, and asari clams, respectively, which were higher than the previous report of 29% and 32% from influents and effluents, respectively [ 18 ]. The differences in isolation rates may be because of the difference in the amount of samples to be cultured in an enrichment broth and that in the geographical circumstances.…”
Section: Discussioncontrasting
confidence: 71%
“…Clostridium perfringens producing CPE and/or CPE in feces from patients has been found in outbreaks [ 3 , 4 , 5 ]. CPE-producing C. perfringens causes both foodborne outbreaks and non-foodborne diarrhea [ 6 , 7 , 8 ] and was isolated from healthy humans, animals with enteric diseases, retail foods, and environmental samples [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, half the type A isolates from the three BGPs carried the cpb2 gene encoding the β2 toxin, which is reported to be associated with diarrheal diseases [19,41]. This result is consistent with those of studies that were conducted on farm animals, in which between 39% and 78.8% frequency of the cpa gene together with cpb2 gene was observed [25,[42][43][44]. Moreover, some isolates recovered from manure and digestate were positive for cpb, etx, and netB genes.…”
Section: Toxinotyping Of C Perfringens Isolatessupporting
confidence: 88%
“…Most of the studies showed type 'A' as dominant strain of the C. perfringens that was also found in this study. Hashimoto et al [22] studied 804 C. perfringens different strains isolated from different sewage water system of humans and animals (chicken, pig, cattle). It was revealed in the study that the C. perfringens isolated from human's sewage water had enterotoxin gene, while, animals sewage C. perfringens isolates did not have enterotoxin gene.…”
Section: Antibiotic Sensitivity Of C Perfringens Type 'A'mentioning
confidence: 99%